2019
DOI: 10.1101/702290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methods matter: your measures of explicit and implicit processes in visuomotor adaptation affect your results

Abstract: Visuomotor rotations are frequently used to study cognitive processes underlying motor adaptation.Explicit aiming strategies and implicit recalibration are two of these processes. A large body of literature indicates that these two processes are dissociable and perhaps even independent components. Various direct and indirect methods have been used to dissociate the two processes.Discrepancies have been found between these different methods. They may arise for different reasons, but one reason may be that the d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Here, participants make open-loop reaches with (implicit and explicit) or without (implicit) the strategy they learned. This process dissociation procedure (PDP 16 ) is consistent with similar tasks 53,55 , has been used in previous studies 17,18,43,56 , and doesn't seem to evoke additional explicit learning unlike other methods [56][57][58] . While explicit learning does not necessarily correspond to external error attribution, it is likely that external error attribution is accompanied by more explicit adaptation.…”
Section: Discussionmentioning
confidence: 76%
“…Here, participants make open-loop reaches with (implicit and explicit) or without (implicit) the strategy they learned. This process dissociation procedure (PDP 16 ) is consistent with similar tasks 53,55 , has been used in previous studies 17,18,43,56 , and doesn't seem to evoke additional explicit learning unlike other methods [56][57][58] . While explicit learning does not necessarily correspond to external error attribution, it is likely that external error attribution is accompanied by more explicit adaptation.…”
Section: Discussionmentioning
confidence: 76%
“…We ask people to make open-loop reaches to targets after adaptation, while either using the strategy they just learned (implicit and explicit), or not using it (only implicit). We use this measurement task as it doesn't seem to evoke additional explicit learning itself, as other methods do (Leow et al, 2017;de Brouwer et al, 2018;Maresch and Donchin, 2019), and to keep results comparable to earlier work from our lab (Modchalingam et al, 2019). While explicit learning does not necessarily lead to external error attribution, it is likely that external error attribution is accompanied with more explicit adaptation.…”
Section: External Error Attribution Reduces Implicit Processesmentioning
confidence: 99%
“…Previous studies have shown that awareness of the nature of the perturbation increases the contribution of explicit learning during adaptation, on top of rather stable implicit learning (Heuer and Hegele, 2008;Benson et al, 2011;Ivry, 2011, 2012;Taylor et al, 2014;Bond and Taylor, 2015;McDougle et al, 2015;Werner et al, 2015;Modchalingam et al, 2019). Here we measure implicit and explicit learning using a process dissociation procedure (PDP; adapted from Werner et al, 2015), which we and others have done before (Neville and Cressman, 2018;Maresch and Donchin, 2019;Modchalingam et al, 2019) and is consistent with findings from a similar task quantifying explicit learning (Hegele and Heuer, 2013). We ask people to make open-loop reaches to targets after adaptation, while either using the strategy they just learned (implicit and explicit), or not using it (only implicit).…”
Section: External Error Attribution Reduces Implicit Processesmentioning
confidence: 99%
“…A similar phenomenon can be observed in other experiments where participants are provided with visual landmarks scattered on either side of the target. When participants use these landmarks to report their intended aiming direction, reporting frequency increases explicit strategy use, but decreases implicit adaptation [66][67][68] . Furthermore, participants themselves exhibit varying degrees of strategy, leading to negative subject-to-subject associations between implicit and explicit learning 15,16,41 (Fig.…”
Section: Competition-driven Enhancement and Suppression Of Implicit Amentioning
confidence: 99%